2017
DOI: 10.1038/s41598-017-12056-5
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The melanocortin signaling cAMP axis accelerates repair and reduces mutagenesis of platinum-induced DNA damage

Abstract: Using primary melanocytes and HEK293 cells, we found that cAMP signaling accelerates repair of bi- and mono-functional platinum-induced DNA damage. Elevating cAMP signaling either by the agonistic MC1R ligand melanocyte stimulating hormone (MSH) or by pharmacologic cAMP induction by forskolin enhanced clearance of intrastrand cisplatin-adducts in melanocytes or MC1R-transfected HEK293 cells. MC1R antagonists human beta-defensin 3 and agouti signaling protein blocked MSH- but not forskolin-mediated enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Briefly, we found that in the context of cell damage and cAMP activation, PKA phosphorylates ATR (17). PKA-mediated ATR phosphorylation on Ser-435 promotes interactions between XPA and ATR and accelerates their recruitment to UV photodamage (17) or platinum adducts (43). Because our earlier work documented that cAMP-enhanced NER depended on ATR-XPA interactions (17), we considered whether other post-translational modifications in ATR or XPA might regulate this pathway.…”
Section: Atr Promotes Sirt1 Localization To Sites Of Uv-induced Dna Dmentioning
confidence: 99%
“…Briefly, we found that in the context of cell damage and cAMP activation, PKA phosphorylates ATR (17). PKA-mediated ATR phosphorylation on Ser-435 promotes interactions between XPA and ATR and accelerates their recruitment to UV photodamage (17) or platinum adducts (43). Because our earlier work documented that cAMP-enhanced NER depended on ATR-XPA interactions (17), we considered whether other post-translational modifications in ATR or XPA might regulate this pathway.…”
Section: Atr Promotes Sirt1 Localization To Sites Of Uv-induced Dna Dmentioning
confidence: 99%
“…This might account, at least partially, for the milder phenotype of Mgrn1 -KO cells newly derived from melan-a6 or B16 cells, as compared with melan-md1 cells derived from mahoganoid mice. Interestingly, human MC1R, a GPCR that activates DNA damage repair in melanocytes [ 52 , 53 , 54 , 55 ] (reviewed in [ 56 , 57 ]) interacts with MGRN1 and promotes its nuclear localization [ 13 ]. Given that activation of MC1R in human melanoma cells stimulates the clearance of DNA strand breaks generated by oxidative stress [ 45 ], a possible involvement of MGRN1 in this MC1R-dependent genoprotective action cannot be ruled out and deserves further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Since, Nrf2-antioxidant signaling has a well-established key role in protection against UV-mediated skin damage [17,56], we further investigated the protective effect of the vitamin D 3 and lumisterol derivatives against UVB-mediated oxidative stress by Nrf2-regulated antioxidant responses. A marked reduction in catalase (P < 0.001, Fig.…”
Section: Increased the Nuclear/cytosolicmentioning
confidence: 99%